Cases in Structural Cardiac Intervention - Varghese, Anitha; Uren, Neal; Ludman, Peter (Springer London : Imprint: Springer, 2017)
This book utilizes case studies to illustrate a variety of percutaneous strategies to treat important cardiac pathology that would previously have mandated cardiac surgery. A desire to minimize the invasiveness of interventions and reduce patient exposure to risk have been the main drivers in developing catheter-based techniques in preference to established surgical methods. Cases in Structural Cardiac Interventions discusses how procedures will continue to increase in popularity as operator expertise grows and technology advances. It provides a useful resource for imaging and interventional cardiologists to work together in developing an inter-disciplinary team skill set that can be adapted towards specific percutaneous intervention in order to ensure optimal patient outcome. - Resumé vydavatel
Keywords: nemoci srdce; srdeční katetrizace; heart diseases; cardiac catheterization; elektronické knihy; případové studie; electronic books; case studies